(untitled) (Economics and region, 2024)
The article analyzes the essence of the concepts “bankruptcy”, “business process” in terms of the enterprise. The level of bankruptcy at enterprises in Germany for 2022-2023 was considered. The causes of bankruptcy were determined, including: illiquidity, excessive indebtedness, loss of competitiveness. The legal framework that regulates the proceedings on the bankruptcy of an enterprise, namely the German Insolvency Code, has been studied. The probability of bankruptcy at “Yagotynsky Butter Plant” LLC was analyzed and the efficiency of business processes was evaluated in the context of the variability of the market environment. The importance of digitalization of business processes in order to prevent the probability of bankruptcy and improve innovative development has been proven. In order to assess the level of business processes at the enterprise, the efficiency of business process indicators was analyzed, strengths and weaknesses were identified using the SWOT analysis matrix, the structure of funding sources was characterized, financial risks were investigated (credit, investment, currency risk, the risk of reducing financial stability and innovative financial risk), which have a great impact on the financial situation, a profitability forecast was made. The essential characteristics of machine learning in a complex approach are considered. The main problems solved by machine learning are indicated. The “bio-flash” technology is characterized, its essence, meaning, scope of use, advantages and disadvantages of its use are determined. The structural elements of the development and the functional purpose of the mechanism are analyzed. Recommendations are given to enterprises that will contribute to the improvement of operational business processes and the production sphere at the factory, and it is also recommended to implement and improve the machine learning method of employees and managers to increase work productivity, competitiveness and financial stability of the enterprise in the future.